Optimal barbell force-velocity profiles can contribute to maximize weightlifting performance - Sandau, I.; Granacher, U (PLOS ONE, 2023)
Maximal barbell power output (Pmax) and vertical barbell threshold velocity (vthres) are major determinants of weightlifting performance. Moreover, an optimal force-velocity relationship (FvR) profile is an additional variable that has the potential to maximize sports performance. The aims of this study were (i) to present a biomechanical model to calculate an optimal FvR profile for weightlifting, and (ii) to determine how vthres, Pmax, and the optimal FvR profile influence theoretical snatch performance (snatchth). To address these aims, simulations were applied to quantify the respective influence on snatchth. The main findings confirmed that at constant vthres and Pmax, snatchth is maximized at an optimal FvR profile. With increasing Pmax and decreasing vthres, the optimal FvR profile becomes more force domi nated and more effective to enhance snatchth. However, sensitivity analysis showed that vthres and Pmax have a larger effect on snatchth than the optimal FvR profile. It can be con cluded that in weightlifting, training protocols should be designed with the goal to improve Pmax and to reduce vthres to ultimately enhance snatchth. Training programs designed to achieve the optimal FvR profile may constitute an additional training goal to further develop weightlifting performance in elite athletes that already present high Pmax levels.